Celebrate with Babs : holiday recipes & family traditions - Costello, Barbara (DK Publishing, 2022)
Your adopted grandmother Barbara Costello, a.k.a. Babs, has collected hundreds of recipes over the decades--all living in her old, wooden recipe box--and has curated her family favorites for your own cherished occasions. With seasonal table spreads, time-tested recipes, and motherly advice, this book bestows the key for elevating all of life's festivities into memorable events. Always know what to serve with dishes for New Year's Day festivities, birthday bashes, summer barbecues, Thanksgiving feasts, and lots of celebrations in between. Start new traditions now, and they will be enjoyed for generations to come.